Social Interaction and Students' Perception of Entrepreneurship in the Context of Authentic Enterprise Exposures - Wing Yan MAN, Thomas; Wai Mui YU, Christina (Senate Hall, 2009)
In researching entrepreneurship education, more attention needs to be given to exploring the educational context and processes involved. With this focus, this study aims to answer two research questions: firstly, do students become more receptive to entrepreneurship after participating in an authentic entrepreneurship education activity, and secondly, how does social interaction within such an activity affect students' perception of entrepreneurship? Using a pre- and post-test method, data were collected from high school students who had participated in an entrepreneurship education activity in Hong Kong which emphasised exposure to authentic enterprise by means of generating a business idea, writing up a business plan, interacting with various business stakeholders and engaging in real trading. The findings suggest that an authentic entrepreneurship education activity should give students the chance to experience the reality of entrepreneurship, particularly the difficulties they are likely to face. This can help them to develop a realistic and wise insight into their choice of an entrepreneurial career. Moreover, it is necessary to maximize students' opportunities for social interaction with the various parties involved throughout entrepreneurship education activities so that a more positive learning experience can be gained. Keywords: students' perception, entrepreneurship, entrepreneurship education, authentic entrepreneurship education activity, social interaction.
Keywords: students’ perception|entrepreneurship|entrepreneurship education|authentic entrepreneurship education activity|social interaction